Language Outcomes of 7-Year-Old Children With or Without a History of Late Language Emergence at 24 Months - Rice, M.; Taylor, Catherine; Zubrick, Stephen (American Speech-Language-Hearing Association, 2008)
Purpose: The aim of this study was to investigate the language outcomes of 7-year-old children with and without a history of late language emergence at 24 months.Method: One hundred twenty-eight children with a history of late language emergence (LLE) at 24 months and 109 children with a history of normal language emergence (NLE) at 24 months participated in direct behavioral assessment of multiple dimensions of language at 7 years. The children were recruited from a prospective cohort study of 1,766 epidemiologically ascertained 24-month-old singleton children.Results: The group mean for the LLE children was within the typical range on an omnibus measure of general language ability and measures of specific dimensions of language. However, a greater percentage of LLE children, relative to NLE children, performed below normative expectations on a measure of general language ability (20% versus 11%), speech (7% versus 2%), syntax (18% versus 8%), and morphosyntax (9%?23% versus 2%?14%), but not vocabulary or semantics.Conclusion: The results provide support for growth models of language impairment that predict that late onset of language foretells a protracted growth difference for some LLE children relative to NLE children, particularly for syntax and morphosyntax.